Evaluation of Government Public Expenditure Performance of the North Sulawesi Province in Increasing Job Opportunities - Junior Semuel Lakat; Anderson Guntur Kumenaung; Hendrik Gamaliel; Marjam Mangantar; Fanda Daisy Prully Rundengan (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
Local governments, as the main actors in public budget management, have a significant role in creating an environment that supports economic growth and expands access to the workforce. This study aims to evaluate the performance of public spending of the North Sulawesi Provincial Government in increasing employment opportunities. The focus of this research is on the analysis of public expenditure allocation and its impact on job creation in the province. The method used is descriptive qualitative research with a library research approach that analyzes public expenditure data, programs implemented, and their impact on job opportunities. The results of the study show that public spending allocated to sectors such as infrastructure, community empowerment, and skills education has a positive impact on creating jobs, especially in the construction, agriculture, and service sectors. However, the challenge faced is the mismatch of the skills provided in training with the needs of the labor market. The study suggests that the government improve the relevance and quality of skills training programs and expand the sectors that receive attention in public spending to create more sustainable and inclusive jobs.